2011
DOI: 10.1002/jcp.22690
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin promotes TGF-β/Smad1 signaling in scleroderma fibroblasts

Abstract: TGF-β is the primary inducer of extracellular matrix (ECM) proteins in scleroderma (systemic sclerosis, SSc). Previous studies indicate that in a subset of SSc fibroblasts TGF-β signaling is activated via elevated levels of activin receptor-like kinase (ALK) 1 and phosphorylated Smad1 (pSmad1). The goal of this study was to determine the role of endoglin/ALK1 in TGF-β/Smad1 signaling in SSc fibroblasts. In SSc fibroblasts, increased levels of endoglin correlated with high levels of pSmad1, collagen, and connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 48 publications
9
72
0
1
Order By: Relevance
“…In agreement with these reports, our present data in the UUO model of tubulo-interstitial fibrosis shows the increase in both Eng mRNA and protein expression in the O kidney ( Figure 1). Several authors demonstrated that Eng promotes fibrosis in different kidney experimental models [15,16,[33][34][35][36][37] and other experimental models of tissue fibrosis in organs such as heart [13,38], liver [39] or skin [40]. Two different Eng isoforms that differs exclusively in the intracellular tail have been reported in both humans [18] and mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these reports, our present data in the UUO model of tubulo-interstitial fibrosis shows the increase in both Eng mRNA and protein expression in the O kidney ( Figure 1). Several authors demonstrated that Eng promotes fibrosis in different kidney experimental models [15,16,[33][34][35][36][37] and other experimental models of tissue fibrosis in organs such as heart [13,38], liver [39] or skin [40]. Two different Eng isoforms that differs exclusively in the intracellular tail have been reported in both humans [18] and mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…2B), suggesting a role for Smad1, which is the key mediator of the Acvrl1/Smad1 axis, in the effects of dexamethasone on TGF-␤ signaling. The Acvrl1/Smad1 axis, which is traditionally considered to be active primarily in the endothelium (29, 48 -50), was demonstrated to be active in NIH/3T3 cells (results not shown) and in fibroblasts (51,52). To examine the functional contribution of Smad1 to the effects of dexamethasone on TGF-␤ signaling, the expression of smad1 was ablated by transfection of NIH/3T3 cells with siRNA directed against smad1, with scrambled siRNA serving as a negative control.…”
Section: Glucocorticoids Inhibit Classical Tgf-␤ Signaling-mentioning
confidence: 92%
“…Both canonical and noncanonical TGF-b signaling pathways are inhibited by Smad6 and/ or Smad7 through a negative feedback loop [119]. Non-canonical signaling occurs through several other intracellular signaling molecules, including but not limited to endoglin/Smad1 [114,115,[120][121][122][123]; TRAF6 [119,[124][125][126]; ERK1/2 [115,121,[127][128][129][130], p38 [131,132] and JunB [133] MAPK; c-Abl [134]; mTOR [134]; PI3K/ AKT [115,128,132,135]; and NF-jB [136]. Much attention has additionally been directed recently to the Wnt/b-catenin pathway, which appears to promote proliferation and migration of lung fibroblasts and profibrotic gene expression [137,138], control TGF-b production and profibrotic activity [139,140], and facilitate EMT through direct interaction between Smad3 and b-catenin [141].…”
Section: Tgf-bmentioning
confidence: 99%